La inseguridad ciudadana en el desarrollo socioeconómico de los habitantes del Barrio 8 de noviembre de la ciudad de Machala - Torres Hidalgo, Juan Carlos (My University, 2020)
The present research worker, deals with citizen insecurity in the socioeconomic development of the November 8 neighborhood of the city of Machala, is a problem that generates economic, social and psychological repercussions that harm the citizen's well-being. Thefts in streets and homes, commercial premises, physical and verbal aggression are the consequences of the insecurity experienced in this sector. The general objective was emphasized in determining the factors that influence the proliferation of citizen insecurity that affect the socioeconomic development of the neighborhood. The epistemological approach that will be followed for the present investigation is the empirical inductive through a mixed methodology that describes and analyzes the problems that are lived in the neighborhood, for this methodology the survey and interview techniques will be used for this way to collect the necessary information. Among the results found by the residents was to gather information that currently the neighborhood November 8 is an insecure site, where theft is the main crime that exists in the neighborhood to not have a police presence antisocials have greater access to commit His misdeeds. For this reason, the strategies that have been proposed to counteract the effects of citizen insecurity are: The development of community assemblies through the co-participation of citizens and the national police to solve the problem, to help, so that residents involve within this assembly and have knowledge of the actions offered by the National Police.
El presente trabajado de investigación, trata la inseguridad ciudadana en el desarrollo socioeconómico del barrio 8 de noviembre de la ciudad de Machala, es un problema que genera repercusiones económicas, sociales y psicológicas que perjudican el bienestar ciudadano. Los robos en calles y domicilios, a locales comerciales, la agresión física y verbal son consecuencias de la inseguridad que se vive en este sector. El objetivo general se enfatizó en determinar los factores que influyen en la proliferación de la inseguridad ciudadana que afectan al desarrollo socioeconómico del barrio. El enfoque epistemológico que se siguió para la presente investigación es el empírico inductivo a través de una metodología mixta permitiendo describir y analizar los problemas que se viven el barrio, para esta metodología se utilizaron las técnicas de encuesta y entrevista para de esta manera recolectar la información necesaria. Entre los resultados encontrados por parte de los moradores se logró recabar información que actualmente el barrio 8 de noviembre es un sitio inseguro, donde los robos es el principal delito que existe en el barrio al no contar con presencia policial los antisociales tienen mayor acceso a cometer sus fechorías. Por este motivo las estrategias que se han planteado para contrarrestar los efectos de la inseguridad ciudadana son: El fortalecimiento asambleas comunitarias a través de coparticipación de la ciudadanía y policía nacional para afianzar el problema, que sirvan de ayuda, para que los moradores se involucren dentro de esta asamblea y tengan conocimiento de las acciones que brinda la Policía Nacional.
Keywords: DESARROLLO; SOCIOECONOMICO; INSEGURIDAD; ROBO